Electroencephalographic biomarkers of epilepsy development in patients with acute brain injury: a matched, parallel cohort study. Issue 11 (27th October 2019) - Punia, Vineet; Fitzgerald, Zachary; Zhang, Xiaoming; Huynh, Huan; Bena, James; Morrison, Shannon; Newey, Christopher R.; Hantus, Stephen
Abstract: Objective: This study was designed to investigate if highly epileptic electroencephalogram (EEG) findings in patients with acute brain injury increase the long‐term risk of epilepsy development. Methods: Adults patients, lacking epilepsy history, with electrographic seizures or lateralized periodic discharges (LPDs) (cases) were identified and matched based on age, mental status, and etiology with the ones lacking any epileptiform activity (controls) on continuous EEG (cEEG) during hospitalization. The primary outcome of clinical seizures after hospital discharge and their antiepileptic drug (AED) status was determined using a telephonic interview. Logistic regression models using generalized estimating equations to account for the matched nature of the data were performed. Results: A total of 70 cases [16 (22.9%) "LPDs only, " 34 (48.6%) "electrographic seizure only, " and 20 (28.6%) "both"] and controls were enrolled. A total of 22 (31.4%) cases developed epilepsy after a mean follow‐up duration of 20.6 ± 5.0 months compared to three (4.3%) controls. After adjusting for cEEG indication and follow‐up duration, the odds of cases developing epilepsy were almost 15 times higher compared to the controls (OR = 14.8, 95% CI = 2.4–92.3, P  = 0.004). This elevated risk was despite a 10 times higher likelihood of cases to be taking AEDs at the last follow‐up (OR = 10.34, 95% CI = 3.7–29, P  < 0.001). Interpretation: Highly epileptic EEG findings in patients with acute brain injury may serve as prognostic biomarkers of epilepsy development. Although prospective studies are required to confirm our findings, it seems that with epilepsy developing in almost one‐third cases in less than 2‐year follow‐up period, such patients may potentially be ideal candidates for epilepsy prevention clinical trials.